Pesantren, Kepemimpinan Kiai, dan Ajaran Tarekat sebagai Potret Dinamika Lembaga Pendidikan Islam di Indonesia - Anita, Anita; Hasan, Mustaqim; Warisno, Andi; Anshori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this research is to acquire a deeper comprehension of Islamic boarding Schools, the traditional Islamic education system, as well as the function of kiai and tarekat as Indonesian religious authority figures. Boarding schools with a religious focus have been operating in Indonesia for hundreds of years, and they've had a significant impact on the development of Islamic education throughout the centuries. Kiai and tarekat are significant components of the traditional education system in Indonesia. They also play an essential part in the growth of Islamic knowledge and culture. The literature is analyzed through the lens of a descriptive methodology in this qualitative study. In order for researchers to obtain data, they must first analyze and assess the quantity of material and theory that has been offered by professionals in the field. This knowledge and theory may be located in the collections and archives of libraries in the form of books, articles from academic journals, periodicals, as well as various sources from the internet and other sources considered suitable to the subject that is being discussed. The analysis of research shows the results that pesantren are Islamic educational institutions that were born culturally from Indonesian culture and are therefore traditional, unique, and original which gives a different color to the education system in Indonesia which is able to provide repertoire and a very important role in fostering society. Islamic boarding Schools cannot function properly without the figure of a Kiai, who makes his presence an absolute requirement. Kiai is a manager who is capable of being a leader and able to regulate the rhythm of the development and survival of the pesantren with his expertise, depth of knowledge, charisma, and skills. Kiai, through the manifestation of tarekat teachings which characterize the value system of ahl al-sunnah wa al-jama'ah, has a significant influence on determining the pattern and trend of scientific traditions as well as the internal policies of Islamic boarding Schools.